The oxygen reduction reaction on [NiFe] hydrogenases. Issue 36 (5th September 2018) - Qiu, Siyao; Olsen, Seth; MacFarlane, Douglas R.; Sun, Chenghua
Abstract : Oxygen tolerance capacity is critical for hydrogen oxidation/evolution catalysts. Abstract : Oxygen tolerance capacity is critical for hydrogen oxidation/evolution catalysts. In nature, [NiFe] hydrogenases show excellent O2 -tolerance and can rapidly reactivate the active site. This work aims to understand the reduction of O2 on the active site of [NiFe] hydrogenases. From the density functional theory (DFT) calculations, the free energy diagram for the oxygen reduction reaction (ORR) has been derived and the rate-determining step is found to be theNi-B toNi-SIb ′ step. Our calculation explains the slow reactivation for theNi-A state compared to theNi-B state, which is due to the particularly stable structure of theNi-A state.